General $n$-dimensional Tauberian problems with application to the Laplace- and Stieltjes transforms - Frennemo, Lennart (MATHEMATICA SCANDINAVICA, 2002)
A general theorem on the closure of translates in certain weighted spaces in $R^n$ is proved and as a consequence a general $n$-dimensional Tauberian theorem. This is applied to the $n$-dimensional Laplace transform and to the one-dimensional Stieltjes- and Weierstrass transforms.